ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP PADA MATERI BANGUN RUANG - Andiyana, Muhamad Arfan; Maya, Rippi; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to determine the ability to think creatively mathematically junior high school students in Ngamprah village with indicators of students' creative thinking ability used is fluency (fleuncy), flexibility, originality and elaboration. the ability to think mathematically creative is the ability to think that aims to create or find new ideas that are different, unusual, original that brings definite and precise results. This research was conducted to 33 students in one of Junior High School in Ngamprah Village by using qualitative descriptive method. Instrument used in the form of 5 items about the ability of students' mathematical creative thinking on the matter of building a flat side room with interviews to students. The conclusion of this research is the ability of mathematical creative thinking of junior high school students in Ngamprah village is still very low.